PREVALENCE OF BOVINE FACIOLOSIS IN HALABA MUNICIPAL ABATTOR SOUTHERN ETHIOPIA - Abdella, Muna; Mhatebu, WubitTafese (International Journal of Research -GRANTHAALAYAH, 2016)
A cross-sectional study was carried out from November 2015 to march 2016 on bovine fasciolosis, to assess the abattoir based prevalence, predominant species of bovine fasciolosis and associated risk factors of the disease in cattle slaughtered in Halaba municipal abattoir. A total of 384 cattle were examined using post mortem examination. Infection rates were (3.64%), 2.34%, 2.08%, and 1.82 % F. gigantic, F. hepatica, mixed and immature respectively with the overall prevalence of 9.88 % (38). F. gigantic was found to be the most prevalent species in cattle of the study area. Multivariable logistic regression analysis showed that the risk of fasciola infection was significantly higher in poor body condition animals than in medium and good body condition animals (p < 0.05). However, in terms of age, sex and breed, no statistically significant difference was found between infected animals (p > 0.05).The present study showed that bovine fasciolosis is one of the important pathogens in cattle in the study area and warrants appropriate disease prevention and control measures and further epidemiological investigations to determine the different agro ecological risk factors on the occurrence of the disease.